Effect of La and Sc Co-Addition on the Mechanical Properties and Thermal Conductivity of As-Cast Al-4.8% Cu Alloys - Zhao-Xi Song (MDPI AG, 2021)
The effects of La and La+Sc addition on mechanical properties and thermal conductivity of Al-4.8Cu alloy were comprehensively studied. The as-cast samples were characterized by optical microscopy (OM), scanning electron microscopy (SEM), X-ray diffraction (XRD) and first-principles methods. The results reveal that the grain morphology of Al-4.8Cu alloy changes from dendrite to fine equiaxed grain with La, La+Sc addition. The average grain size of Al-Cu-La (Al-4.8Cu-0.4La) and Al-Cu-La-Sc (Al-4.8Cu-0.4La-0.4Sc) decreased by 37.2% (70.36 μm) and 63.3% (119.64 μm) respectively compared with Al-Cu (Al-4.8Cu). Al-Cu-La has the highest elongation among the three which is 34.4% (2.65%) higher than Al-Cu. Al-Cu-La-Sc has the highest ultimate tensile strength and yield strength which are 55.1% (80.9 MPa) and 65.2% (62.1 MPa) higher than Al-Cu, respectively. The thermal conductivity of Al-Cu-La and Al-Cu-La-Sc is 10.0% (18.797 W·m−1·k−1) and 6.5% (12.178 W·m−1·k−1) higher than Al-Cu alloy respectively. Compared with Al-Cu, Al-Cu-La has less shrinkage and porosity, the presence of Al4La and AlCu3 contribute a lot to the decrease of specific heat capacity and the increase of plasticity and toughness. The porosity of Al-Cu-La-Sc does not significantly decrease compared with Al-Cu-La, the presence of Al3Sc and AlCuSc bring about the increase of specific heat capacity and brittleness.